Problem dan Kontroversi Kelas Akselerasi di Sekolah: Analisis Solutif untuk Pendidikan Berkualitas - Miswanto Miswanto (Jurnal Studi Pendidikan Agama Islam, 2025)
The acceleration class program is designed to meet the educational needs of students with exceptional intelligence and talents, enabling them to complete formal education within a shorter period. Despite its considerable potential to optimize the intellectual development of gifted students, the implementation of acceleration classes in schools continues to face various challenges and controversies across academic, psychological, and social dimensions. This study aims to identify the main problems and controversies surrounding the implementation of acceleration classes and to formulate solution-oriented strategies to promote high-quality and sustainable education. This study adopts a library research approach by analyzing relevant scholarly sources, including peer-reviewed journals, books, and academic documents. Data analysis was conducted systematically through several stages, including the determination of units of analysis, data coding, theme identification, and conclusion drawing. The findings indicate that the primary issues in acceleration classes include rigid and overloaded curricula, limited teacher competence, and disruptions to students’ psychological and social well-being. Furthermore, controversies arise concerning program effectiveness, unequal access to education, and potential social tension within the school environment. This study proposes solutions in the form of adaptive curriculum development, enhancement of teacher capacity, strengthening of counseling services, and the implementation of continuous program evaluation. These findings are expected to serve as a reference for the development of more holistic acceleration class policies and practices that prioritize student well-being.